Pemanfaatan Instagram @houseofchic Sebagai Media Komunikasi Pemasaran - Rahmadani, Nia; Riauan, Muhd Ar. Imam (Riauan Consulting and Communication, 2022)
This study aims to determine the use of Instagram as online shop marketing communication medium on the @houseofchic account. Houseofchic is an online shop that sells clothes with unique and updated models for the youth segment. The research method used is descriptive qualitative with data collection in-depth interviews to nine informants, two owners and seven consumers @houseofchic. The theory used in this research is marketing communication concept. Results showed that the use of Instagram as an online shop marketing communication medium on the @houseofchic account by adding followers, producing goods, taking pictures, editing photos, captioning items, marking followers, and maximizing the number of likes. Supporting factors for the use of Instagram are consistent routines in the use of Instagram, while the inhibiting factors are adjustments to the use of Instagram features, intense competition, lack of consumer trust.